O'RTACHA SALMOQLI USULDA MAHSULOT TANNARXI TO'G'RISIDAGI HISOBOT - Xudaynazarova Dilnoza,; Abdukarimov Bobur, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the preparation of the production cost report using the weighted average method. The study focuses on the theoretical and practical aspects of product cost calculation, its role in accounting, and the importance of cost measurement methods  in  financial  reporting.  In  particular,  the  essence  of  the  weighted  average method,  its  application  procedure,  and  its  significance  in  determining  the  cost  of materials and finished goods in the production process are analyzed. The article also explores the stages of preparing a product cost report based on the  weighted  average  method,  practical  calculations,  and  their  impact  on  financial results. The findings show that this method allows for simplified and accurate cost calculation, contributing to a more reliable assessment of the financial condition of an enterprise.